Financial Management Efficiency in the Context of Improving School Quality at State Senior High School 11 in Bengkulu City (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study examines the efficiency of financial management in improving school quality at SMA Negeri 11 Bengkulu City, with a focus on planning, implementation, and evaluation processes. The study responds to the limited empirical evidence on how efficiency principles are applied in school financial management within decentralized education systems. A descriptive qualitative approach was employed, using interviews, observations, and documentation as data collection techniques. Data were analyzed through the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that financial planning is conducted systematically based on actual needs and collaborative decision-making. Budget implementation prioritizes essential programs that directly support learning quality and student services, while evaluation and reporting processes emphasize transparency, accountability, and alignment between planning and realization. Furthermore, efficient financial management contributes to improved learning facilities, teacher professional development, and program sustainability. This study provides practical insights for school leaders and policymakers in strengthening accountable and quality-oriented financial management practices.